Issues in economics today - Guell, Robert C. (New York : McGrwa Hill LLC, 2021)
"This book is designed for a one-semester issues-based general education economics course, and its purpose is to interest the nonbusiness, noneconomics major in what the discipline of economics can do. Students of the "issues approach" will master the basic economic theory necessary to explore a variety of real-world issues. If this is the only economics course they ever take, they will at least gain enough insight to be able to intelligently discuss the way economic theory applies to important issues in the world today. Until the first edition of this book was published, instructors who chose the issues approach to teaching a one-semester general economics course had to compromise in one of the following ways: they could (1) pick a book that presents the issues but that is devoid of economic theory; (2) pick a book that intertwines the issues with the theory; (3) ask students to buy two books; or (4) place a large number of readings on library reserve"--
Includes index.
Ages 18+
Grades 10-12
Keywords: Economics